2003
DOI: 10.1046/j.1526-4610.2003.03133.x
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Headache: Biopsychosocial Comparisons With Multiple Control Groups

Abstract: This study confirmed the distress seen in this understudied population of persons with headache and highlights areas of focus for proper assessment and treatment of those with headache and who have had an accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
3
15
1
Order By: Relevance
“…This result supports the tendency to repress and introject anger, which is consistent with the hypotheses about the role of psychosomatic mechanisms in migraine patients [16,17,18] and with the literature describing the dynamics of obsessive control typical of some of these patients [65, 66]. Since no differences emerged for the other STAXI scales, the patients’ main characteristic seems the skill in monitoring, preventing and removing anger; though this mechanism does not seem specific of migraine patients but it may also be shared by patients suffering from other types of cephalalgia [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result supports the tendency to repress and introject anger, which is consistent with the hypotheses about the role of psychosomatic mechanisms in migraine patients [16,17,18] and with the literature describing the dynamics of obsessive control typical of some of these patients [65, 66]. Since no differences emerged for the other STAXI scales, the patients’ main characteristic seems the skill in monitoring, preventing and removing anger; though this mechanism does not seem specific of migraine patients but it may also be shared by patients suffering from other types of cephalalgia [12].…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have stated coping difficulties [14, 15], psychosomatic mechanisms, alexithymia [16,17,18,19,20] and a certain personality structure [21] to be typical of migraine patients. All these issues are related; for example, new trends in alexithymia research suggest that alexithymic individuals display avoidant behaviors (related to certain personality constructs and attachment patterns) and interpersonal problems with a reduced capacity to use social interactions for affect regulation (coping difficulties) [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…One of the difficulties in examining this particular group of patients is that chronic PTH has not been studied as widely as other forms of headache [23]. This study confirmed that this population of patients with PTH often are suffering more distress than other groups of patients who have experienced trauma, but are headache-free [23].…”
Section: Psychologic Factorssupporting
confidence: 60%
“…Other risk factors for developing chronic PTHA include female gender, lower socioeconomic status, and prior history of headaches [7,8,10,11,15]. Psychiatric disorders are increased in patients with PTHA and contribute to headache chronicity, headache frequency, and headache-related disability [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%